Two essays on macroeconomics - Türk, Tuğçe. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
This thesis is composed of two essays on macroeconomics. In the ﬁrst one, the aim is to understand the role of the informal sector in determining countries’ access to the world technology frontier as well as to their own technology frontiers. It is found that incorporating the informal economy alters the measurement of the formal TFP signiﬁcantly. For2006, thedifferencebetweenTFP obtained fromclassical onesector model and the formal TFP obtained from the model with informality is 25%. Both formal and informal labor efﬁciencies are positively related to income levels of countries. When technology frontiers of each country are investigated, it is found that access to the world technology frontier results in 38% decrease in income differences among countries. In the second essay, I investigate the behavior of the marginal cost of public funds (MCF) using different taxes under the presence of informality. To this end, I build a dynamic general equilibrium model with formal and informal sectors and allow the government to use consumption, capital, and labor income taxes to raise the revenue needed to ﬁnance government purchases. Then, I use the simulations of the model to evaluate how the MCF is associated with informality level of countries. Finally, using country-level data on taxes, we calibrate and measure MCF for a panel of developed and developing countries.
Keywords: Macroeconomics.; Monetary policy.